Real-world effectiveness of live attenuated influenza vaccines (LAIV) and inactivated influenza vaccines (IIV) in children from 2003 to 2023: a systematic literature review and network meta-analysis - Anke L. Stuurman; Joshua Enxing; Aura V. Gutiérrez; Christen M. Gray; Ingrid T. Sepúlveda-Pachón; Egbe Ubamadu; Allyn Bandell; Sylvia Taylor; Georges El Azzi; Wilhelmine Meeraus (Expert Review of Vaccines)
Introduction Circulating influenza strains, vaccine effectiveness (VE), and vaccine recommendations vary over time. A systematic literature review (SLR), random effects meta-analysis (REMA), and network meta-analysis (NMA) estimated absolute VE (aVE) and relative VE (rVE) of LAIV and IIV in children/adolescents from initial LAIV approval in 2003.Methods Northern Hemisphere studies (2003–2023) with children ≤19 yrs were included. A modified Newcastle-Ottawa Scale assessed risk-of-bias. REMA estimated aVE and three-node NMA (LAIV-IIV-unvaccinated) estimated rVE over three periods: 2003–04 to 2008–09 (pre-2009 A(H1N1) pandemic); 2010–11 to 2016–17 (post-2009 pandemic); 2017–18 to 2022–23 (post-LAIV strain-selection optimization).Results One hundred and nine studies included. aVE of LAIV and IIV against any influenza was similar (~50%) in each period. Effectiveness of LAIV vs. IIV against influenza types/subtypes was comparable except (1) greater effectiveness with IIV for A(H1N1) in 2010–11 to 2016–17 (rVE −46% [95% CI: −57, −33]); (2) greater effectiveness with LAIV for influenza B in 2017–18 to 2022–23 (rVE 196% [95% CI: 73, 406]). In 2017–18 to 2022–23, effectiveness of LAIV and IIV against A(H1N1) was similar (rVE 10% [95% CI: −35, 87]).Conclusions LAIV and IIV have demonstrated comparable effectiveness against any influenza in children.